The Effectiveness of a Cognitive Behavioral Guidance Program to Reduce Intellectual Distraction Among Female University Students (Journal of the College of Basic Education, 2025)
The current study aims to identify the effectiveness of a cognitive behavioral counseling program in reducing intellectual emptiness among female university student, The researcher used a quasi-experimental design, and built a scale of intellectual emptiness, where the number of paragraphs reached (40) paragraphs. The application sample was chosen intentionally from the Department of Psychological Counseling and Educational Guidance and the Department of Life Sciences, with (10) female students for the experimental and control groups. Then the researcher designed a cognitive behavioral guidance program according to the "Meckenbaum" theory to reduce the intellectual vacuum according to the Borders and Drury model. The researcher used the statistical bag to analyze the data and the researcher concluded that the cognitive behavioral guidance program is effective in reducing the intellectual vacuum. Through the result that showed that there are statistically significant differences between the average ranks of the students’ scores in the experimental and control groups on the intellectual emptiness scale in the pre- and post-tests, and in light of the results of the current research, the researcher came up with a set of recommendations and proposals.